A interação tutor-alunos em EAD: protagonistas de ações de leitura e escrita - Soares, Inaldo Firmino (2010)
Set on the foundations of Applied Linguistics which focusses on language activities from different theretical focus, this paper is the outcome of a research on the language actions of postgraduate students (Specialization Courses),observed in the interaction with their tutors and peers, by means of digital hypertext, in a Learning Virtual Environment a Hiper Digital Context. It also studies the way these actions reflect the development and improvement of students verbal language. The topic was studied by means of differentiated authors within Sociodiscursive Interactionism such as: (BRONCKART, 1999, 2006a, 2006b, 2008; DOLZ, PASQUIER E BRONCKART, 1993; DOLZ e SCHNEUWLY, 1998; MACHADO, 2005; MATENCIO, 2007; PEREIRA, 2006, 2007, 2009a, 2009b, 2010). This theory presents as its main theoreticians, Vygostsky (1998, 1987) in the development field, and Bakhtin (2003, 1986), in the language field. To these two authors all thought architecture is supported by social interaction mediated by language. As it is a qualitative research, besides revising the literature we had to observe the students in their interaction with their tutors/teachers and their peers, by means of written messages that circulated in the virtual learning environment. The observed situations offered us subsides to analyse questions related to the way they read, wrote; how their ideas were organized and their knowledge was constructed. The tutor-student language interactions constituted meaningful contributions for the activities of reading and writing by the subjects involved, and if it had occurred in a more conscious form, being clear the role language activities exert over the construction of the conscious thought, the contribution would be more expressive. The reading and writing activities, that have always existed together, have been centered on the thematic content, reflecting a view of reading as decoding activity, to the detriment of a discursive conception that considers not only the skills and competences related to the content, but also the linguistic materiality of the text and its enunciation situation. Starting from a broader notion of reading and writing, considered as social practices, and observing the language interactions of the subjects of this research, especially the tutors with their guidance and interventions on the written activities of the students, some gaps were found. Not all the parameters of social and individual order, being them external, linked to the conditions of text production, or internal, related to the cognitive processing activated during the writing production, have been contemplated. Regarding to the processing of ideas, both the activities proposed by the tutors/teachers and the students' interactions on the e-foruns as well as their text productions showed that actions such as searching, creation, evaluation, decision and selection of ideas were relatively contemplated. What was not present in a more expressive form, especially from the tutors, were the actions of ranking, ordering, concatenating and articulating, that assures the textualization mechanisms and contribute for the thematic coherence of the text, fundamental guidances when written activities were asked, because, independently of their levels and the teaching manner - face or distance education - in which they find themselves, the difficulties are the same. Another action revealed by the results of this study, a wider one, is the massive and systematic investment in the basic and continuing formation of teachers of Portuguese, particularly, but also from other disciplines, as the work with reading and writing are interrelated to the fields of History, Geography, Philosophy, etc. Teachers' training, thus, must start from the comprehension of the complexity of the written language practices, a type of comprehension that imposes a pedagogy of literacy, including digital, that comes to overlap to the pedagogy of the theme or to a genre teaching program that does not contemplate their pragmatic and sociocommunicative aspects. In this sense, this study leaves its contribution for the possible effectiveness of an interface between Applied Linguistics, that focuses in language activities from different theoretical perspectives, and the Distance Education (EaD), both undergraduation and post-graduation courses, with their organizers, webdesigns, tutors, content teachers and students. It is also our intention, by having done this research, to contribute for the spread of the Sociodiscursive Interactionism in Brazil, interdisciplinary theoretical perspective whose studies originate and radicalize in the conception that every thought architecture is sustained in relation to the other, through social interaction, mediated by language. The research points to the need of an adviser/counsellor, a professional from the Applied Linguistics Area, in conceiving, structruing and building up (LVEs) (Learning Virtual Environment) courses where interaction acts effectively: tutor students / students-students reading and writing may constitute the middle and the end of knowledge construction helping in the development and improvement of verbal language.